2023
DOI: 10.3390/polym15030664
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Cellulose Microfibers from Colombian Cocoa Pod Husk via Chemical Treatment with Pressure Effects

Abstract: One of the current challenges is to add value to agro-industrial wastes, and the cocoa industry generates about 10 tons of cocoa pod husks in Colombia for each ton of cocoa beans, which are incinerated and cause environmental damage. This study characterized the Colombian cocoa pod husk (CPH) and to isolate and characterize cellulose microfibers (tCPH) extracted via chemical treatment and pressure. Chemical and physical analyses of CPH were performed, and a pretreatment method for CPH fibers was developed, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 92 publications
1
8
0
Order By: Relevance
“…This enhancement is due to the removal of amorphous components that consist of lignin and hemicellulose according to the treatments used. The results align with previous research that showed that bleaching treatments increase crystallinity by removing lignin [ [102] , [103] , [104] ]. The CrI values for SPF after bleaching were higher than those for pomelo fruitlets (44.26%) and rice straw fibers (62.4%), as reported by He et al [ 81 ] and Thakur et al [ 105 ] correspondingly.…”
Section: Resultssupporting
confidence: 91%
“…This enhancement is due to the removal of amorphous components that consist of lignin and hemicellulose according to the treatments used. The results align with previous research that showed that bleaching treatments increase crystallinity by removing lignin [ [102] , [103] , [104] ]. The CrI values for SPF after bleaching were higher than those for pomelo fruitlets (44.26%) and rice straw fibers (62.4%), as reported by He et al [ 81 ] and Thakur et al [ 105 ] correspondingly.…”
Section: Resultssupporting
confidence: 91%
“…The FTIR spectrum for the untreated fibers revealed the presence of a band around 3330 cm −1 , which occurs due to the presence of OH groups of polysaccharides [38]. The bands observed in the range from 2990 to 2820 cm −1 are attributed to C-H bonds that exist in lignin, hemicellulose, and cellulose [39].…”
Section: Fourier Transform Infrared Spectroscopymentioning
confidence: 98%
“…However, the value of this practice is contested, as it may have an overall negative impact by allowing proliferation of the “ cacao disease trilogy”. , Some cocoa farmers are considering preparing and selling CPH for alternative uses if collection is feasible and the price is sufficient . In terms of the current technology associated with CPH biorefining, reports have focused on the analysis and application of carbohydrate components, , particularly studies on CPH pectin. Here, while a number of fractions from the biomass are considered, we focus instead on the CPH lignin component. Limited precedent for the isolation of lignin from CPH is available which is surprising given that current estimates of lignin content place it at around 20% of the weight of the husk. …”
Section: Introductionmentioning
confidence: 99%
“… 33 , 34 Some cocoa farmers are considering preparing and selling CPH for alternative uses if collection is feasible and the price is sufficient. 35 In terms of the current technology associated with CPH biorefining, reports have focused on the analysis and application of carbohydrate components, 36 , 37 particularly studies on CPH pectin. 38 42 Here, while a number of fractions from the biomass are considered, we focus instead on the CPH lignin component.…”
Section: Introductionmentioning
confidence: 99%